Research on valorisation of spent garnets as addition in cementitious materials – preliminary experimental evaluation. Issue 1 (1st July 2022) - Baeră, C; Chendeş, R; Gruin, A; Perianu, A; Vasile, V; Varga, L
Abstract: Abrasive waterjet (AWJ) material processing represents a relatively new and extremely efficient method in the specific industries, implying various applicability areas, attributed to different materials, with different properties and domains of use. Besides numerous advantages of the AWJ cutting and generally of the material processing techniques, they also involve the waste generation: the abrasive sands are converted into sludge material, collected into recipients and further on, after natural drying, they become waste dumps randomly deserted. The enlargement of the AWJ techniques in the latest years determines the corresponding increase of the associated Garnet wastes (Spent Garnets, SG), thus leading towards the clear need of identifying opportunities for their recycling and valorisation. Aggregates are basic raw materials in the production of concrete, mortar and plasters, composite cementitious and/or cement-free materials (geopolymer concrete) in the building materials and generally, in the construction industry. The rapid growth of the population, recorded mainly in urban areas, determines an increasing demand on housing facilities and consequently, on concrete production and aggregates consumption. Aggregates and sand, mainly exploited from riverbeds or quarries, represent exhaustible natural resource for which substitution solutions need to be found, in order to control and reduce their extraction from the natural landscape. Considering the superposition of this independent cause and effect situations, the rapid growth of Spent Garnets (SG) landfills, generated by AWJ processes, and, on the other hand, the need to substitute the natural aggregate in construction industry, a reliable solution could emerge from the potential valorisation of SG wastes as partial or even complete substitution of sands / aggregates in the composition of construction materials. The present paper offers a preliminary overview regarding the possibility of incorporating SG wastes of local production in usual cement-based materials, as partial substitute of the aggregate, for the double purpose of waste management implementation and natural resources protection, on the transition path towards the implementing the Circular Economy (CE) concept in the Romanian industry.